Last Christmas - Kenyon, Sherrilyn, 1965- (Kenyon, Sherrilyn, 1965- Chronicles of Nick., 2023)
"The holiday season is always interesting when you live in a world with paranormal entities. As a Daeve demon, Caleb Malphas never really understood why humans wanted to celebrate anything. Until the day a human saves his life. Lilliana isn't just human, she's the one person capable of taming a vicious demon whose sole goal is to end the world and claim it for his masters. Caleb fights her at every turn, but in the end, he can't deny what she comes to mean to him. Vowing to never again battle for his demonic overlords, he lays down his sword to spend eternity in the human world. But his enemies won't allow them to live in peace. They return with a vengeance to claim everything he's learned to care about. It's an unforgivable act. Centuries later as he joins Nick Gautier and their friends for a very special Christmas gathering, he finally learns the real meaning of giving ... and receives the best gift of his immortal life."--